Linking natural gas markets: is LNG doing its job? - Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The increase in liquefied natural gas trade has accelerated the integration of previously segmented markets in North America, Europe, and Asia. This paper provides evidence on the integration of the transatlantic natural gas market. We test the theoretical proposition that in integrating markets commodity prices should move closer than before. Using 2,059 pairs of daily spot prices for natural gas in North America and Europe we investigate price dynamics covering the period from 1999 until 2008. We apply the Kalman Filter technique to gain detailed information on trends inherent over time. Results suggest an increasing convergence of spot prices on either side of the Atlantic Basin.
Keywords: L95; Q49; F15; 330; Market integration; spot markets; LNG; natural gas; Erdgas; Flüssiggas; Preis; Marktintegration; Atlantischer Ozean; Nordamerika; Europa